THE EFFECT OF JOB PLACEMENT AND CAREER DEVELOPMENT ON PERFORMANCE MEDIATED BY EMPLOYEE MOTIVATION AT BAPPERIDA WEST SULAWESI - Muh Saleh; Arthur Sitaniapessy; Prabawa Eka Soesanta (MANAJEMEN DEWANTARA, 2026)
This study aims to analyze the impact of job placement and career development on employee performance at Bapperida across West Sulawesi, mediated by employee motivation. The research approach is quantitative, with a sample of 154 employees working at Bapperida across West Sulawesi. Data was collected using questionnaires and analyzed using Structural Equation Modeling (SEM). The results indicate that job placement significantly affects both employee performance and motivation. Career development has a significant effect on employee motivation but does not have a direct impact on performance. Employee motivation plays an important role as a mediator in the relationship between job placement and employee performance. Based on these findings, it is recommended that Bapperida across West Sulawesi pay more attention to job placements that align with employee competencies and enhance relevant career development programs to boost motivation and performance.